Clinician approach to cardiopulmonary exercise testing for exercise prescription in patients at risk of and with cardiovascular disease. Issue 20 (9th June 2022) - D'Ascenzi, Flavio; Cavigli, Luna; Pagliaro, Antonio; Focardi, Marta; Valente, Serafina; Cameli, Matteo; Mandoli, Giulia Elena; Mueller, Stephan; Dendale, Paul; Piepoli, Massimo; Wilhelm, Matthias; Halle, Martin; et al.
Abstract : Exercise training is highly recommended in current guidelines on primary and secondary prevention of cardiovascular disease (CVD). This is based on the cardiovascular benefits of physical activity and structured exercise, ranging from improving the quality of life to reducing CVD and overall mortality. Therefore, exercise should be treated as a powerful medicine and critical component of the management plan for patients at risk for or diagnosed with CVD. A tailored approach based on the patient's personal and clinical characteristics represents a cornerstone for the benefits of exercise prescription. In this regard, the use of cardiopulmonary exercise testing is well-established for risk stratification, quantification of cardiorespiratory fitness and ventilatory thresholds for a tailored, personalised exercise prescription. The aim of this paper is to provide a practical guidance to clinicians on how to use data from cardiopulmonary exercise testing towards personalised exercise prescriptions for patients at risk of or with CVD.